Borrelia burgdorferi initiates early transcriptional re-programming in macrophages that supports long-term suppression of inflammation. - Tanja Petnicki-Ocwieja; Julie E McCarthy; Urmila Powale; P Kent Langston; Jennifer D Helble; Linden T Hu (PLoS Pathogens, 2023)
Borrelia burgdorferi (Bb), the causative agent of Lyme disease, establishes a long-term infection and leads to disease manifestations that are the result of host immune responses to the pathogen. Inflammatory manifestations resolve spontaneously despite continued bacterial presence, suggesting inflammatory cells become less responsive over time. This is mimicked by in vitro repeated stimulations, resulting in tolerance, a phenotypic subset of innate immune memory. We performed comparative transcriptional analysis of macrophages in acute and memory states and identified sets of Tolerized, Hyper-Induced, Secondary-Induced and Hyper-Suppressed genes resulting from memory induction, revealing previously unexplored networks of genes affected by cellular re-programming. Tolerized gene families included inflammatory mediators and interferon related genes as would be predicted by the attenuation of inflammation over time. To better understand how cells mediate inflammatory hypo-responsiveness, we focused on genes that could mediate maintenance of suppression, such as Hyper-Induced genes which are up-regulated in memory states. These genes were notably enriched in stress pathways regulated by anti-inflammatory modulators. We examined one of the most highly expressed negative regulators of immune pathways during primary stimulation, Aconitate decarboxylase 1 (Acod1), and tested its effects during in vivo infection with Bb. As predicted by our in vitro model, we show its inflammation-suppressive downstream effects are sustained during in vivo long-term infection with Bb, with a specific role in Lyme carditis.